The use of Technology towards Science Needs in Salafi Islamic Boarding Schools - Muhammad Rizal; Muhammad Osama; Saiful Bahri (IJECA (International Journal of Education and Curriculum Application), 2024)
The aim of this research is to characterize the scientific educational technology integration system in Salafi Islamic boarding schools. The purpose of this investigation is to characterise the phenomenon of scientific education technology integration in Salafi boarding schools. Researchers used qualitative descriptive methods. Santri, school principals, teachers and Dayah leaders were examined. This research was attended by one school principal, four educator, and five grade 10 students of Dayah Aljamiah Vocational School and Dayah MUDI Bireuen. Interviews, observations and documentation are research tools. Data was obtained through observation, interviews and documentation. Analysis involves collecting, reducing, presenting, and drawing conclusions. This study tested four factors to ensure data accuracy: trustworthiness, transferability, dependability, confirmability. The results of this research show that (1) Aceh's Dayah Salafi has integrated science and technology into their environment through vocational schools; (2) Dayah Salafi Al Jamiah Al-Aziziyah and MUDI led the Yellow Book learning revolution with learning technologies; and (3) Dayah has taught kids that religious and general knowledge are equal. The results of this research show that Dayah Salafi teachers in Aceh have made structured efforts to change the way their students learn science and technology.